2022
DOI: 10.1111/ele.14059
|View full text |Cite
|
Sign up to set email alerts
|

Explosive networking: The role of adaptive host radiations and ecological opportunity in a species‐rich host–parasite assembly

Abstract: Many species‐rich ecological communities emerge from adaptive radiation events. Yet the effects of adaptive radiation on community assembly remain poorly understood. Here, we explore the well‐documented radiations of African cichlid fishes and their interactions with the flatworm gill parasites Cichlidogyrus spp., including 10,529 reported infections and 477 different host–parasite combinations collected through a survey of peer‐reviewed literature. We assess how evolutionary, ecological, and morphological par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 192 publications
1
16
0
Order By: Relevance
“…The gill‐infecting dactylogyrids of tilapia belong to Cichlidogyrus and Scutogyrus , and are characterised by a haptor bearing two pairs of anchors (whereas there is only one pair in gyrodactylids), a V‐shaped ventral transversal bar (in contrast to the ventral bar of members of Gyrodactylus , which possesses a membrane), a dorsal transversal bar with two auricles (in contrast to the simple dorsal bar in Gyrodactylus ) and seven pairs of marginal hooks (compared to 8 in Gyrodactylus ; Figure 9c–e, g). Cruz‐Laufer et al 289 identified that numerous gill‐infecting species have been co‐introduced outside continental Africa and are reported in the peer‐reviewed literature from Latin America, Asia, Australia or Madagascar. Five of these have been mentioned as co‐introduced in at least 15 publications.…”
Section: Parasitic Infections Of Tilapiamentioning
confidence: 99%
See 2 more Smart Citations
“…The gill‐infecting dactylogyrids of tilapia belong to Cichlidogyrus and Scutogyrus , and are characterised by a haptor bearing two pairs of anchors (whereas there is only one pair in gyrodactylids), a V‐shaped ventral transversal bar (in contrast to the ventral bar of members of Gyrodactylus , which possesses a membrane), a dorsal transversal bar with two auricles (in contrast to the simple dorsal bar in Gyrodactylus ) and seven pairs of marginal hooks (compared to 8 in Gyrodactylus ; Figure 9c–e, g). Cruz‐Laufer et al 289 identified that numerous gill‐infecting species have been co‐introduced outside continental Africa and are reported in the peer‐reviewed literature from Latin America, Asia, Australia or Madagascar. Five of these have been mentioned as co‐introduced in at least 15 publications.…”
Section: Parasitic Infections Of Tilapiamentioning
confidence: 99%
“…tiberianus Paperna, 1960, which normally infect coptodonine tilapia occur on other tilapia and cichlids in their introduced range. These changes in host range can occur wherever tilapias are translocated, because ecological opportunity and host phylogenetic history determine the host range 289,344 . Introduced populations can be free of gill monogeneans, such as O .…”
Section: Parasitic Infections Of Tilapiamentioning
confidence: 99%
See 1 more Smart Citation
“…intra-host speciation) and expansion of host repertoires (e.g. host switches) [8]; this fluctuation is also considered a likely occurrence in monogenean flatworms [6, 10]. However, identifying patterns for intra-host speciation or host switching in the absence of DNA sequence data poses a major challenge.…”
Section: Discussionmentioning
confidence: 99%
“…African cichlids are well-known for their spectacular adaptive radiations [108,114,118], and their role as model for evolutionary research [114]. The cichlid- Cichlidogyrus species network is the most extensively described host-parasite network from a species-rich host radiation [10]. A recent meta-analysis counted 477 different host-parasite combinations in this study system [10].…”
Section: Introductionmentioning
confidence: 99%